Analysis of Figurative Language in Taylor Swift’s Song “Fearless” Album - I Dewa Ayu Devi Maharani Santika; Ni Nyoman Deni Ariyaningsih; Felisia Elsawati (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This study aims to identify and analyze the types of figurative language and the meaning of figurative language found in the song lyrics of Taylor Swift's album